2021
DOI: 10.1609/aaai.v35i6.16610
|View full text |Cite
|
Sign up to set email alerts
|

A Novice-Reviewer Experiment to Address Scarcity of Qualified Reviewers in Large Conferences

Abstract: Conference peer review constitutes a human-computation process whose importance cannot be overstated: not only it identifies the best submissions for acceptance, but, ultimately, it impacts the future of the whole research area by promoting some ideas and restraining others. A surge in the number of submissions received by leading AI conferences has challenged the sustainability of the review process by increasing the burden on the pool of qualified reviewers which is growing at a much slower rate. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Another study offers novice reviewers a more guided introduction to the different stages of the reviewing process, such as how to lead a discussion among reviewers, to help novices write better reviews. The results showed that with this guidance on the reviewing stages, novice reviewers could deliver more "above expectation" reviews [80]. However, their guidance is only limited to introducing the different parts of the reviewing process, such as rebuttal and discussion, and providing novices opportunities to ask expert questions on the general process [80].…”
Section: Related Work 21 Practices and Challenges Related To Academic...mentioning
confidence: 99%
See 4 more Smart Citations
“…Another study offers novice reviewers a more guided introduction to the different stages of the reviewing process, such as how to lead a discussion among reviewers, to help novices write better reviews. The results showed that with this guidance on the reviewing stages, novice reviewers could deliver more "above expectation" reviews [80]. However, their guidance is only limited to introducing the different parts of the reviewing process, such as rebuttal and discussion, and providing novices opportunities to ask expert questions on the general process [80].…”
Section: Related Work 21 Practices and Challenges Related To Academic...mentioning
confidence: 99%
“…The number of papers in research communities has increased exponentially in recent years [85]. While this may be positively viewed as an acceleration of scientific progress, the disparity between growth rates of the submission and reviewer pools also creates more burden for reviewers [60,76,79,80]. To avoid overloading reviewers, conferences need to find new sources of reviewers as there are not enough experienced reviewers to review all papers [80].…”
Section: Related Work 21 Practices and Challenges Related To Academic...mentioning
confidence: 99%
See 3 more Smart Citations